- 1-800-665-6601
- [email protected]

This can be better understood by the suitable examples. The examples are shown below:-

In the first step we will separate the addition symbol as shown below:

(22 x^22/ 11 x^11) + (44 x^44/ 11 x^11)

Now we will divide the constant term with constant and variable with variable, we get

= 2 x^ (22-11) + 4 x^ (44-11)

= 2 x^11 + 4 x^33

So (22 x^22 + 44 x^44) / 11 x^11 = 2 x^11 + 4 x^33

In the first step we will separate the addition symbol as shown below:-

(49 x^8/ 7 x^2) + (63 x^ 4/ 7 x^2)

Now we will divide the constant term with constant and variable with variable, we get

= 7 x^ (8-2) + 9 x^ (4-2)

= 7 x^6 + 9 x^2

So (49 x^8 + 63 x^4) / 7 x^2 = 7 x^6 + 9 x^2.